2022
DOI: 10.1029/2022ef002751
|View full text |Cite
|
Sign up to set email alerts
|

A High‐End Estimate of Sea Level Rise for Practitioners

Abstract: Sea-level rise (SLR) is a long-lasting consequence of climate change because global anthropogenic warming takes centuries to millennia to equilibrate for the deep ocean and ice sheets. SLR projections based on climate models support policy analysis, risk assessment and adaptation planning today, despite their large uncertainties. The central range of the SLR distribution is estimated by process-based models. However, risk-averse practitioners often require information about plausible future conditions that lie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 164 publications
(307 reference statements)
0
20
0
1
Order By: Relevance
“…A more sophisticated approach would be preferred in future, particularly when the studies disagree substantially (see Discussion). Other studies have considered the effect of assuming full correlation or independence of contributions on total sea level projections: for example, van de Wal et al (2022) found that assuming independence reduced their global mean sea level projections at 2300 by 1.8 m under the very high emissions scenario SSP5-8.5, compared with full correlation, and by 0.3 m under the SSP1-2.6 scenario that we present here.…”
Section: Total Global Mean Sea-levelmentioning
confidence: 80%
See 1 more Smart Citation
“…A more sophisticated approach would be preferred in future, particularly when the studies disagree substantially (see Discussion). Other studies have considered the effect of assuming full correlation or independence of contributions on total sea level projections: for example, van de Wal et al (2022) found that assuming independence reduced their global mean sea level projections at 2300 by 1.8 m under the very high emissions scenario SSP5-8.5, compared with full correlation, and by 0.3 m under the SSP1-2.6 scenario that we present here.…”
Section: Total Global Mean Sea-levelmentioning
confidence: 80%
“…Projections under SSP1-2.6 and SSP2-4.5 could be sufficient for a first assessment in these case studies, because SSP1-2.6 corresponds to the upper target of the Paris Agreement and SSP2-4.5 is often used for (2021). A scenario is also needed for stress testing of critical infrastructure, but this may be already covered to a large extent by the low-likelihood, high-impact (i.e., high-end) projections to 2150 provided by the AR6 (IPCC, 2021a, 2021b) and others (van de Wal et al, 2022).…”
Section: Potential Application Of Multi-centennial Projectionsmentioning
confidence: 99%
“…Uncertainties associated with the East Antarctic ice sheet, these authors find, play an important role only for longer timescales and high warming. van de Wal et al (2022) generate high-end estimates of sea-level rise for risk-averse practitioners. Coproduced by scientists and practitioners using a framework introduced by Stammer et al (2019), the estimates generated by this study are distinct from, but complementary to, the corresponding values reported in the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (Fox-Kemper et al, 2021) because different approaches are taken to quantify the contribution of land-ice wastage to future sea-level rise.…”
mentioning
confidence: 99%
“…Bamber et al (2022) argue that uncertainties on future Greenland surface mass balance largely stem from uncertain albedo processes, such as changing cloud cover, surface darkening and debris cover, and the seasonality of air temperature and precipitation, whereas uncertainties on future ice discharge from West Antarctica are mainly controlled by ice-shelf buttressing and initiation of marine ice sheet and ice cliff instabilities. Also important, underscore van de Wal et al (2022), are uncertainties associated with melt-albedo and height-surface mass balance feedbacks, atmospheric rivers and blocking events, tipping points and timing of ice-shelf collapse around Antarctica, ice-ocean interactions and circulation of circumpolar deep water, and basal friction near grounding lines, among other processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation